Global patterns and trends in ischemic stroke burden attributable to particulate matter pollution: changes from 1990 to 2021 and projections from 2022 to 2050 - Erman Wu; Erman Wu; Riqing Su; Tong Tang; Jiakun Li; Maimaitili Mijiti; Yandong Li; Gaocai Zhang; Minghao Lian; Yongtao Zhang; Guohua Zhu; Dangmurenjiafu Geng (Frontiers in Public Health)
BackgroundStroke was the third leading cause of global deaths in 2021, linked to air pollution, especially particulate matter (PMP). Research shows that ischemic strokes are more affected by air pollution than hemorrhagic strokes. This study aims to evaluate the disease burden, trends, and future projections of ischemic stroke associated with PMP using the latest data.MethodsWe used data from the 2021 Global Burden of Disease study to analyze the burden of ischemic stroke attributable to PMP from 1990 to 2021. Joinpoint regression was used to assess the trends (Average Annual Percentage Change, AAPC). Meanwhile, the Bayesian Age – Period – Cohort modeling method was used to project the burdens until 2050.ResultsGlobally, PMP-related ischemic stroke caused 905,600 deaths and 18.3 million DALYs in 2021, the highest levels in the past three decades PMP-related ischemic stroke deaths increased by 32.94% (1990–2021), yet ASDR declined by 46.65% (AAPC: −2.09, 95% CI: −2.45 to −1.72). Ambient particulate matter pollution (APMP) accounted for 66.6% of the burden in 2021 (vs. 45.9% in 1990), disproportionately affecting middle- and high-SDI regions. Conversely, household air pollution (HAP)-related burden declined but remained concentrated in low-SDI regions (80–82.5% in 2021). East Asia, South Asia, and Southeast Asia bore the highest absolute burdens, while Western Europe achieved the steepest ASR declines (AAPC for deaths: −6.55%). Projections to 2050 indicate rising ASRs. There was a negative correlation between SDI and ASRs, with APMP rising in middle-SDI nations and HAP persisting in low-SDI areas. Significant gender differences exist in the disease burden of PMP – induced ischemic stroke. Males generally have higher mortality rates and DALYs than females across most age groups, and the peak male mortality has been delayed over the past 30 years.ConclusionThis global analysis underscores the urgent need for targeted pollution control strategies to address the dual burden of ischemic stroke driven by APMP in high- and middle-income regions and HAP in low-resource settings, emphasizing the critical role of tailored interventions to mitigate health disparities and achieve sustainable development goals.